Nuclear proteins from lactating mammary glands bind to the promoter of a milk protein gene. - Lubon, H (1987)
The gene for the whey acidic protein (WAP) is expressed specifically in the lactating mammary glands of rodents. We present evidence that nuclear proteins from mammary epithelial cells form a multiple nucleoprotein complex with the WAP gene promoter/upstream region. As monitored by mobility shifts, nuclear proteins from lactating mammary glands and from the mammary cell line MCF-7 form four high affinity complexes with a fragment spanning the region between nucleotides -175 and -88. Nuclear proteins from liver and HeLa cells generate only three high affinity complexes. DNAaseI and ExonucleaseIII protection confirmed the binding of mammary nuclear proteins to specific sequences in the WAP gene upstream region. This is the first report to describe the interaction of nuclear proteins from lactating mammary glands with cognate binding sites in the promoter/upstream region of a milk protein gene. The possibility of the binding sites being candidates for cis-acting regulatory elements governing the regulated expression of the WAP gene is discussed.